Evaluation of canthaxanthin in eggs and its subsequent dietary risks to Chinese consumers. Issue 2 (1st February 2021) - Xue, Xueting; Fan, Lixia; Dong, Yanjie; Yuan, Xuexia; Wang, Lei; Yang, Fabin; Zheng, Yan; Zhao, Shancang
ABSTRACT: Canthaxanthin is a colourant widely used in medicine, food and cosmetics, which is closely related to human eye dysfunction. The EU determines that the daily acceptable intake of canthaxanthin (ADI) is 0.03 mg canthaxanthin per kg body weight. In order to protect people's diet health and avoid the occurrence of food safety accidents, this paper measured the content of canthaxanthin in 114 egg samples sourced from different regions of China using ultrahigh-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The dietary exposure assessment method was used to evaluate the dietary risk to Chinese consumers. Results showed that the content of canthaxanthin varies significantly across regions of origin, with eggs produced in Beijing having a lower amount than those from other regions. The average dietary exposure of children (2–10 years old) was 0.242 0.653 μg/(kg bw∙d), and the dietary exposure of 95/97.5/99 percentile was 0.246 1.779 μg/(kg bw∙d). The maximum exposure was 3.089 μg/(kg bw∙d), and its risk quotient was 0.103 (<1), which was an acceptable risk. For the teenager group (11–18 years old), the average dietary exposure was 0.141 0.247 μg/(kg bw∙d), and the dietary exposure at the 95/97.5/99 percentile was 0.143 0.671 μg/(kg bw∙d), presenting an acceptable risk. For adults, the dietary risk of eating eggs with canthaxanthin is the lowest among the three age groups.